The effects of foot position on lower extremity kinematics during single leg squat among adolescent male athletes - Azhar, Norain Mohd; Affandi, Nor Fatinah; Zuhan, Mohamad Saufi; Shaharudin, Shazlin (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2019)
Objectives: The purpose of this study was to investigate the effect of transverse plane foot position on lower limb kinematics during a single leg squat. Methods: This was a cross-sectional study conducted among highly-trained male athletes. Only participants who showed normal knee valgus during a drop landing screening test were recruited. Twelve junior athletes performed single leg squats while maintaining a knee flexion angle of 60. The squats were executed in three foot positions: neutral (0), adduction (10), and abduction (þ10). Three-dimensional motion analysis was used to capture the lower extremity kinematics of the participants’ preferred limb. The hip and knee kinematics in the sagittal, frontal, and transverse planes during squatting were compared across the three foot positions using oneway ANOVA. Results: The participants showed a normal range of dynamic knee valgus (5.31.6). No statistically significant differences were observed in hip flexion (p ¼ 0.322), adduction (p ¼ 0.834), or internal rotation (p ¼ 0.967) across different foot positions. Similarly, no statistically significant differences were observed in knee flexion (p ¼ 0.489), adduction (p ¼ 0.822), or internal rotation (p ¼ 0.971) across different foot positions. Conclusion: Small changes in transverse plane foot position do not affect lower extremity kinematics during single leg squat in highly trained adolescent males with normal dynamic knee valgus. Our findings may provide guidance on safer techniques for landing, pivoting, and cutting during training and game situations.